2018
DOI: 10.1007/s11606-018-4335-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Future Chronic Opioid Use Among Hospitalized Patients

Abstract: Our model accessed EHR data to predict 79% of the future COT among hospitalized patients. Application of such a predictive model within the EHR could identify patients at high risk for future chronic opioid use to allow clinicians to provide early patient education about pain management strategies and, when able, to wean opioids prior to discharge while incorporating alternative therapies for pain into discharge planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 49 publications
(57 reference statements)
7
73
0
Order By: Relevance
“…Other significant predictors of long‐term opioid prescribing include longer cancer survivorship, later years of diagnosis, female sex, urban residence, lung cancer diagnosis, disability as the original reason for Medicare enrollment, Medicaid eligibility, and one or more comorbidities. Similar to prior studies, a history of depression and drug abuse also predicted prolonged opioid prescribing . Cancer diagnosis at an older age, Hispanic ethnicity, and being opioid naïve strongly predicted lower odds of opioid prescribing among older cancer survivors.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Other significant predictors of long‐term opioid prescribing include longer cancer survivorship, later years of diagnosis, female sex, urban residence, lung cancer diagnosis, disability as the original reason for Medicare enrollment, Medicaid eligibility, and one or more comorbidities. Similar to prior studies, a history of depression and drug abuse also predicted prolonged opioid prescribing . Cancer diagnosis at an older age, Hispanic ethnicity, and being opioid naïve strongly predicted lower odds of opioid prescribing among older cancer survivors.…”
Section: Discussionsupporting
confidence: 74%
“…Similar to prior studies, a history of depression and drug abuse also predicted prolonged opioid prescribing. [27][28][29] Cancer diagnosis at an older age, Hispanic ethnicity, and being opioid naïve strongly predicted lower odds of opioid prescribing among older cancer survivors. Among opioidnaïve cancer survivors, diagnosis from 2004 to 2008 was the strongest predictor of long-term opioid use, while the strongest predictor for all cancer survivors was a history of drug abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple demographic and clinical factors were associated with increased risk of chronic opioid use after hysterectomy, including older age, abdominal or laparoscopic/robotic hysterectomy, comorbidities, tobacco use, substance use disorders, certain pain conditions, and use of prescription psychiatric medication use (Table ). Our findings were consistent with other studies which showed that these factors increase the risk of chronic opioid use after major cardiac, thoracic, abdominal and pelvic procedures, or specific surgeries, including cesarean delivery, hysterectomy, hip or knee arthroplasty, spine, or bariatric surgeries . These findings underscore the importance of considering the individual patient's pain management needs; risk factors for opioid misuse at the time of opioid prescribing after hysterectomy and other surgical procedures; and importance of medical care, monitoring, and follow up postoperatively.…”
Section: Discussionsupporting
confidence: 91%
“…For many women, their first exposure to prescription opioids often occurs during the postoperative period, which makes this a potential target for strategies to reduce the risk of chronic opioid use . Several observational studies suggest that surgery is a risk factor for chronic opioid use . Two studies have examined the relationship between the initial opioid prescribing characteristics and chronic opioid use in the postoperative setting and arrived at contradictory conclusions .…”
Section: Introductionmentioning
confidence: 99%
“…Log‐binomial regression was used to model risk for subsequent LTO with an array of independent variables including sociodemographic characteristics, medical diagnoses, and prescription medications that are potentially associated with long‐term use and commonly query‐able within electronic medical records . Diagnoses were identified by ICD‐9 and ICD‐10 codes from outpatient encounters during the year prior to opioid initiation.…”
Section: Methodsmentioning
confidence: 99%